2014
DOI: 10.1039/c4ra10813b
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient dinuclear Cu(ii) chemosensor for colorimetric and fluorescent detection of cyanide in water

Abstract: A novel dinuclear copper chemosensor selectively binds cyanide over a wide range of inorganic anions, enabling it to detect cyanide in water up to 0.02 ppm which is 10 times lower than the EPA standard for drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The third unbound carboxylate group in each binding mode is H-bonded with the OH group of the citrate (OH···O = 2.533 and 2.620 Å in A and B modes, respectively). For each of the optimized geometries, the binding energy (ΔE) was calculated with a 6–311 g(d, p) basis as described earlier 41 , yielding an attractive ΔE of −70.79 kcal/mol for mode A and −73.07 kcal/mol for mode B. The most attractive binding energy for mode B reflects the preferred orientation of the citrate with the dinuclear copper complex in mode B.…”
Section: Resultsmentioning
confidence: 99%
“…The third unbound carboxylate group in each binding mode is H-bonded with the OH group of the citrate (OH···O = 2.533 and 2.620 Å in A and B modes, respectively). For each of the optimized geometries, the binding energy (ΔE) was calculated with a 6–311 g(d, p) basis as described earlier 41 , yielding an attractive ΔE of −70.79 kcal/mol for mode A and −73.07 kcal/mol for mode B. The most attractive binding energy for mode B reflects the preferred orientation of the citrate with the dinuclear copper complex in mode B.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic receptors (SR) are architecturally designed by chemists for selective recognition of a variety of substrates, mimicking many critical enzymatic activities involved in biology [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The unique functional groups present in such molecules can be potentially used for designing drugs to target specific activities in a human body [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28] Using a supramolecular approach, there has been an immense interest in developing efficient chemical sensors for oxalate by colorimetric and fluorescence methods. [29][30][31][32][33][34][35][36][37][38][39][40][41] Previous studies demonstrated that the complexes of certain metal ions including zinc, [32][33] copper, [34][35][36][37][38][39] nickel, [40][41] and calcium [42] can be used as suitable chemosensors for detecting an oxalate anion in solution.…”
Section: Introductionmentioning
confidence: 99%